Implementasi Pendidikan terhadap Pola Kebiasaan Anak Berkebutuhan Khusus (Studi Kasus Kehidupan Septi Anak diduga Down Syndrome di Dusun Jetis Desa Mororejo Kec. Tempel Sleman Yogyakarta) - Rizka Amalia (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2019)
In a simple child with special needs is a child whose development is different from normal children in general. Children with special needs have some characteristics, which are usually referred to as disorders or abnormalities, one of the disorders or abnormalities is a down syndrome. Down syndrome can happen to anyone and anywhere, be it from poor or rich families, no exception it happens to Septi 12-year-old child who was forced to daily hear the taunts of his peers and parents who forbid his children who Normal to get along with Septi. Septi's life is one example of the many cases of Down Syndrome that occur in children in Indonesia. From the phenomenon that then makes the importance of knowing and reviewing the Pattern of Habits of Children with Special Needs (Case Study of Life Septi Children allegedly Down Syndrome in Dusun Jetis Desa Mororejo Kec. Tempel Sleman Yogyakarta)